PATTERNS OF GRAMMATICAL ERRORS IN STUDENTS’ THESIS - Faisal Hakim; Untung Waluyo; Henny Soepriyanti (Journal of English Education Forum (JEEF), 2022)
Grammar is badly needed by all thesis writers in order that they can produce good outputs as expected by the English Education Department. Therefore, the study aims to reveal the types of grammatical errors and to identify the most types of grammatical errors in students’ thesis. In this research, the researcher employed a descriptive qualitative method. In this study, the researchers only focused on analyzing the grammatical errors in English students’ thesis at the University of Mataram using a surface strategy taxonomy. The researchers used a purposive sampling method to gather the data. The data were derived from students’ theses submitted between 2018 and 2020. There were a total of 9 theses studied for the purpose. The data were classified into 4 determined categories suggested by the theory of Surface Strategy Taxonomy, i.e. (1) Omission, (2) Addition, (3) Misformation and (4) Misordering. The result of the study shows that the theses under investigation contained the four categories of errors. There were a total number of 275 errors found in students’ theses. The most common types of errors were in Misformation (49.81%) and the least one was Misordering (0.72%). Implication of the present study is provided succinctly in the concluding part of this article.